Praktik vigilantisme digital di media sosial dalam konflik antarkelompok - Isnaini, Muhamad; Sarwoprasodjo, Sarwititi; Kinseng, Rilus A.; Kholil, Kholil (Jurnal Studi Komunikasi, 2020)
This research was conducted based on the frequent conflicts in Johar Baru sub-district, Central Jakarta. Tawuran or brawls has become a daily routine in that particular sub-district. This study aimed to analyse practices of digital vigilantism on social media amid intergroup conflict. Researchers explored Facebook accounts of several groups that are often involved in a conflict. This study used a qualitative content analysis method. The results revealed that digital vigilantism practices found were security, supervision, control, discipline, and punishment of one group against other groups through social media, where punishment, i.e. name-calling, and shaming are the most common practices, so that conflicts from the virtual world lead to conflicts in the real world.